2022
DOI: 10.3390/d15010014
|View full text |Cite
|
Sign up to set email alerts
|

Global Overview of Modern Research Based on Ellenberg Indicator Values

Abstract: The ecological indicator values are the most common and sufficiently effective method of habitat assessment. The aim of our research review is to analyze current studies from 2020 to 2022 in which researchers have used Ellenberg indicator values to address a variety of problems. We limited the study to papers that are published in journals indexed by Scopus and Web of Science. The total number of records examined was 358. The number of records selected was 98. Visualization of the distribution of studies by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 122 publications
0
11
1
Order By: Relevance
“…We found that the use of this methodology gives good results in the studies of different plant communities in different countries. The geography of the use of the Landolt indicator values is somewhat different from the geography of the use of the Ellenberg indicator values analyzed in our previous study [8]. As with Ellenberg indicator values, we found no limitations to the use of Landolt indicator values when studying a wide range of plant communities.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…We found that the use of this methodology gives good results in the studies of different plant communities in different countries. The geography of the use of the Landolt indicator values is somewhat different from the geography of the use of the Ellenberg indicator values analyzed in our previous study [8]. As with Ellenberg indicator values, we found no limitations to the use of Landolt indicator values when studying a wide range of plant communities.…”
Section: Discussioncontrasting
confidence: 74%
“…However, it is practically impossible to evaluate these factors by one-time accounting without long-term stationary studies, since daily, seasonal and year-to-year variability of indicators will not be taken into account. Ecological indicator values make it possible to assess the cumulative impact of factors, since they link the signs of vegetation and gradients of the leading environmental factors [8]. The assessment of habitats by ecological indicator values has a number of advantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we examined shifts in individual herb layer species and plant functional groups. Ellenberg-type ecological indicator values of plant species (Ellenberg et al 1992) are frequently used tool to infer environmental changes and to measure the magnitude and direction of changes in plant community composition in resurvey studies as they correspond fairly well with environmental factors measured in the eld (Diekmann 2003;Zolotova et al 2023). The whole concept is based on the premise that changes in species presences/absences and abundances translate to community-level increases or decreases in EIVs and that this likely indicate changes in environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Julve adapted them for France (Julve, 2015). Ellenberg's EIVs and their derivatives are still actively used by ecologists, frequently in forest systems (Zolotova et al., 2023). These ordinal‐scale EIVs from Ellenberg or Julve are mainly based on expert knowledge and field observations, whereas new sets of “biogeographic” EIVs are statistically derived from spatial occurrences and distribution maps covering large spatial extents, such as EcoPlant (Gégout et al., 2005) and ClimPlant (Vangansbeke et al., 2021).…”
Section: Introductionmentioning
confidence: 99%